Microwave processing of oil palm wastes for bioenergy production and circular economy: Recent advancements, challenges, and future prospects - Shin Ying, Foong; Yi Herng, Chan; Serene Sow, Mun Lock; Bridgid Lai Fui, Chin; Chung Loong, Yiin; Kin Wai, Cheah; Adrian Chun Minh, Loy; Peter Nai Yuh, Yek; William Woei Fong, Chong; Su Shiung, Lam (Elsevier Science, Ltd., 2022)
The valorization and conversion of biomass into various value-added products and bioenergy play an important role in the realization of sustainable circular bioeconomy and net zero carbon emission goals. To that end, microwave technology has been perceived as a promising solution to process and manage oil palm waste due to its unique and efficient heating mechanism. This review presents an in-depth analysis focusing on microwave-assisted torrefaction, gasification, pyrolysis and advanced pyrolysis of various oil palm wastes. In particular, the products from these thermochemical conversion processes are energy-dense biochar (that could be used as solid fuel, adsorbents for contaminants removal and bio-fertilizer), phenolic-rich bio-oil, and H2-rich syngas. However, several challenges, including (1) the lack of detailed study on life cycle assessment and techno-economic analysis, (2) limited insights on the specific foreknowledge of microwave interaction with the oil palm wastes for continuous operation, and (3) effects of tunable parameters and catalyst’s behavior/influence on the products’ selectivity and overall process’s efficiency, remain to be addressed in the context of large-scale biomass valorization via microwave technology.